Analisis Kualitas Aplikasi Edukasi "History Of Indonesia Independence" Menggunakan Standar ISO 25010 - Abror, A. Faiq (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
his study aims to analyze the software quality of the educational application "History of Indonesia Independence" based on the ISO 25010 standard, focusing on the indicators of functional suitability, usability, and portability. The testing method employed questionnaires to measure functional suitability and usability, along with direct testing on various smartphone devices to assess portability. The results indicate that the application was deemed "Highly Eligible" in terms of functional suitability with a score of 86%. In the aspect of usability, the application received an "Eligible" predicate with a score of 82.9%. Meanwhile, the portability test proved that the application could run successfully on ten devices with different Android operating system versions. Overall, this application has met the established software quality standards. Recommendations for future development include enhancing the usability aspects to achieve a higher eligibility level and conducting ongoing portability testing.